(3fehPL ef JaSjQ eYGde GdJfRjds - (3CHh eMeO GdMSjf Hf eSYhO GdHZhis; (3CHh eMeO GdMSjf Hf eSYhO Hf eMeO GdaQGA GdHZhj GdTGaYj eMjj GdSfI,J (B516 (3g` s ((3aGWeI HfJ GdMSf s)
(3ChdgG (B:s
(3ShQI Bd YeQGf eGFJG BjI eOfjI bhdg JYGdi (B( (3Bde Gddg dG Edg EdG gh (B) (3bGd GdcdHi hGdQHjY Hf CfS hZjQgeG fRdJ gPg GdBjGJ ai haO fLQGf s
(3BNQgG (B:s
(3Ke fRd ai WQjb MLI GdhOGY (B( (3jSJaJhfc bd Gddg jaJjce ai GdcdGdI (B) (3aSejJ CjI GdUja Ke fRdJ hgh hGba HYQaI (B( (3Gdjhe CcedJ dce Ojfce (B) (3aYGT HYOgG CMO hYTQjf jhekG hGddg SHMGfg CYde s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs